STOPPING THE ARMS RACE: DEALING WITH IMPEDIMENTS TO ACTION - Miller, Joanna (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1987)
There is a great danger that Canadians will be overwhelmed by the controlled information coming to them from the United States, and will automatically endorse their defence policies. Observers of the superpowers, who come from countries other than the U.S. and the U.S.S.R. often interpret events in a way different from the one Canadians get from the U.S. news media. Canadians would do well to question more the interpretations given to world events by others, to create their own policy, and to be seen as an independent nation, weighing in on the side of reconciliation. RÉSUMÉ Il y a de grandes chances pour que les Canadiens soient submergés par l'infonnation contrôlée qui leur parvient des États-Unis, et qu'ils avalisent automatiquement la politique de défense des Américains. Les observateurs du jeu des superpuissances qui sont originaires de pays autres que les États Unis et l'URSS donnent souvent des événements une interprétation différente de celle qui est proposée aux Canadiens par les organes de presse américains. Les Canadiens avaient tout intérêt à mettre en question davantage les interprétations des événements mondiaux qui leur sont livrées par d'autres, à créer leur propre politique et à projeter l'image d'une nation indépendante qui a son mot à dire dans le débat sur la réconciliation.